Determinants of prices for cow-calf pairs - Parcell, J.L.; Hiner, F.D.; Schroeder, Ted C. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
A study of price determinants for cow-calf pairs was undertaken at a local Kansas auction company during 1993. Cow breed, age, health, condition score, horns, frame size, and whether the cow h ad been bred back impacted cow-calf pair values, as well as calf weight, health, and frame score. Addition ally, pairs per pen significantly impacted prices. Young healthy cows with healthy large calves received the highest prices.
Keywords: Beef; Cow-calf pair prices; Cow-calf traits